Taking Dogs Into the Office: A Novel Strategy for Promoting Work Engagement, Commitment and Quality of Life - Hall, Sophie Susannah; Mills, Daniel Simon (Frontiers in Veterinary Science, 2019)
Despite growing interest in “take your dog to work” days and the wellbeing benefits associated with interactions with a friendly dog (e.g. animal-assisted activities), there has been little quantification of the benefits of this. We analysed responses to work-related (work engagement, turnover intention, work-based friendship acuity, social media use and work-related quality of life) and dog-related (pet dog attachment and dog general health) scales from 749 employees. The predominantly female sample was comprised of243 employees who brought their dog to work (167 = ‘often’ brought dog to work; 76 = ‘sometimes’ brought dog to work), the remaining 506 did not bring their dog to work. Employees who ‘often’ took their dog to work reported higher than average work engagement on all factors (vigour, dedication, absorption, total), with significant differences reported in comparison to those who ‘sometimes’ (vigour and total) and ‘never’ (vigour, dedication, absorption, total) took their dog to work. Turnover intention was also significantly lower and work-based friendship acuity higher in the group of employees who ‘often’, compared to ‘never’, took their dog to work. Benefits of bringing your dog to work were also observed in terms of work-related quality of life, with higher scores on general wellbeing, home-work interface, job career-satisfaction, control at work, working conditions and overall work quality of life in those who ‘often’ compared to ‘never’ take their dog to work. Employees who ‘never’ took their dog to work reported lower use of social media during break times. We also identified factors which may be important to consider in developing dogs-in-the-workplace policies; dog-demographics including weight (i.e. size), breed-type and training may be important to consider in defining the ideal office dog and deserve further research. Given the need to improve employee wellbeing and satisfaction to promote effective business performance and economic gain, these results have important implications for office based businesses considering allowing dogs in the workplace.